2010
DOI: 10.1021/la100928t
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Self-Structuring in a Nanofluid Film Spreading on a Solid Surface

Abstract: Liquids containing nanoparticles (nanofluids) exhibit different spreading or thinning behaviors on solids than liquids without nanoparticles. Previous experiments and theoretical investigations have demonstrated that the spreading of nanofluids on solid surfaces is enhanced compared to the spreading of base fluids without nanoparticles. However, the mechanisms for the observed enhancement in the spreading of nanofluids on solid substrates are not well understood. The complex nature of the interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 42 publications
8
107
1
Order By: Relevance
“…Al-Anssari et al [28] tested the surface modification with SEM-EDS and atomic force microscopy (AFM) measurements. It was observed that the distribution of the NPs on the surface were homogeneous after nano-modification ( Figure 11) [50,51]. wettability of the sandstone cores from a strongly oil-wet to a strongly water-wet condition.…”
Section: Wettability Alterationmentioning
confidence: 99%
“…Al-Anssari et al [28] tested the surface modification with SEM-EDS and atomic force microscopy (AFM) measurements. It was observed that the distribution of the NPs on the surface were homogeneous after nano-modification ( Figure 11) [50,51]. wettability of the sandstone cores from a strongly oil-wet to a strongly water-wet condition.…”
Section: Wettability Alterationmentioning
confidence: 99%
“…SEM produces high-resolution images for even the smallest structures at nano-scale as high magnifications are used during image processing. SEM investigations on rock substrates with respect to wetting have been reported by several researchers [88][89][90]. AFM also enables imaging of the surface of the samples at extremely high resolutions using a sharp tip for probing the surface features of the samples.…”
Section: Sem and Afm Imagingmentioning
confidence: 99%
“…It has been shown that the number of layers of nanoparticles (i.e., thickness) decreased in a stepwise pattern towards the triple line edge (see Figure 1b). The pattern of nanoparticle distribution at the triple line was influenced by many factors including nanoparticles materials and morphology, particle concentration, nanoparticle surface charge, solid-liquid-gas materials and film depth in the triple region [62][63]. In one study, the rate of spreading of the nanofluid film was shown to be a function of the nanoparticle concentration and the oil drop volume.…”
Section: Effect Of Nanoparticles On the Behavior Of Triple Linementioning
confidence: 99%